2009
DOI: 10.1097/hjh.0b013e328329bbf4
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of atherosclerotic renal artery stenosis in risk groups: a systematic literature review

Abstract: RAS has a high prevalence in risk groups, especially in those with extrarenal atherosclerosis, end-stage renal failure and heart failure. These findings are important when screening for RAS or prescription of an angiotensin converting enzyme inhibitor or angiotensin-II receptor blocker is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
104
3
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(117 citation statements)
references
References 64 publications
(92 reference statements)
2
104
3
8
Order By: Relevance
“…We performed systematic RA in consecutive AMI patients, regardless of other risk factors suggesting RAS (severe hypertension, PAD, or abdominal bruits). Data showed concordant values of RAS prevalence in AMI (16.6%) to those reported in well‐recognized risk groups (suspected renovascular hypertension5, 30—14.1%, hypertension and diabetes mellitus31—17.1%, chronic CAD5, 32, 33—9.1% to 10.8%) but lower values than in patients with chronic heart failure34—54.1%, aortic abdominal aneurysm35—38%, end‐stage renal disease36—40.8%. Differences between reports are driven by inclusion of patients with different stages of atheromatous disease and inflammation.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…We performed systematic RA in consecutive AMI patients, regardless of other risk factors suggesting RAS (severe hypertension, PAD, or abdominal bruits). Data showed concordant values of RAS prevalence in AMI (16.6%) to those reported in well‐recognized risk groups (suspected renovascular hypertension5, 30—14.1%, hypertension and diabetes mellitus31—17.1%, chronic CAD5, 32, 33—9.1% to 10.8%) but lower values than in patients with chronic heart failure34—54.1%, aortic abdominal aneurysm35—38%, end‐stage renal disease36—40.8%. Differences between reports are driven by inclusion of patients with different stages of atheromatous disease and inflammation.…”
Section: Discussionsupporting
confidence: 66%
“…The relationship between extent of CAD and RAS has been previously evaluated in elective patients37: the number of diseased coronary arteries roughly multiplies by 5 the prevalence of RAS 5. In our study, the degree of CAD was a strong predictor for RAS in multivariate analysis, reflecting progressive stages of multisite disease.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In a meta-analysis of patients with atherosclerotic risk factors such as hypertension, DM, CHD, CKD or PAD, the prevalence of RAS has been reported to be 15.4%. 16 In multiple series of PAD cases, the rates of RAS varied from 12.0 to 45.5%, with a pooled prevalence of 25.3%. 16 Wilms et al 17 found a 22% prevalence of RAS X50% in patients with PAD (mean age 62.4 years old), and Amighi et al 1 recently reported a prevalence of RAS X60% on angiography of 15.6% in patients with PAD (mean age 70.6 years old).…”
Section: Discussionmentioning
confidence: 99%
“…16 In multiple series of PAD cases, the rates of RAS varied from 12.0 to 45.5%, with a pooled prevalence of 25.3%. 16 Wilms et al 17 found a 22% prevalence of RAS X50% in patients with PAD (mean age 62.4 years old), and Amighi et al 1 recently reported a prevalence of RAS X60% on angiography of 15.6% in patients with PAD (mean age 70.6 years old). Thus, our results for the rate of RAS in Japanese patients with PAD are similar to those found in previous studies.…”
Section: Discussionmentioning
confidence: 99%